Issues of arms control in transatlantic relations (1963–1975) - V. A. Veselov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2024)
Against the backdrop of the rapid degradation and destruction of the international security architecture dating back to the Cold War, the problems of arms control in general and the proliferation of nuclear weapons in particular assume new significance. There is an increasing need to search for new multilateral forms of interstate cooperation in this area, which would make it possible to adapt the established models of arms control to the realities of the emerging polycentric world order. In this regard, the history of relations between the members of the military-political blocs during the Cold War could offer some valuable lessons. This article examines three cases related to the deliberations between NATO allies on the prohibition of nuclear weapons tests, the preparation of the Treaty on the Non-Proliferation of Nuclear Weapons, and negotiations on the mutual reduction of armed forces and conventional armaments in Central Europe. The study shows that though the United States had the final say in developing solutions to arms control problems in all three cases, the positions of its NATO allies significantly affected both the course of the negotiation and the content of the agreements. The author concludes that one of the main lessons to be learnt from the discussions of 1963–1975 is what ignorance of the lessons from the past can lead to. Disregard for the experience of the interwar negotiations did not allow then to unleash the full potential of a multilateral inter-bloc dialogue on arms control. Now this lesson is becoming more relevant than ever before.